Adventitious Bursitis Overlying an Osteochondroma of the Humerus Facing the Thoracic Wall - Zeynep Maras Ozdemır; Mustafa Karakaplan; Aysegul Sagir Kahraman; Nese Karadag (Case Reports in Radiology)
One of the complications of osteochondromas is the development of a bursa over the cartilaginous cap. We report a 15-year-old boy with a rapidly expanded adventitious bursitis overlying an osteochondroma of the humerus facing the thoracic wall, a location not previously reported for such bursa formation. Magnetic resonance imaging readily showed adventitious bursitis overlying the osteochondroma, thereby dispelling concerns for malignant transformation.